An insect symbiotic virus promotes the transmission of a phytoarbovirus via inhibiting E3 ubiquitin ligase Sina - Wang, Hui; Zhang, Jieting; Liu, Runfa; Li, You; Du, Yu; Wei, Taiyun (PLoS pathogens, 2025)
Co-infection with symbiotic viruses and arboviruses with synergistic effects in insect vectors are common in nature, but the underlying mechanism remains elusive. Here, we identify a novel symbiotic virus, leafhopper Recilia dorsalis bunyavirus (RdBV), which enhances the transmission efficiency of cytorhabdovirus rice stripe mosaic virus (RSMV, a plant rhabdovirus) in field. RSMV infection activates the expression of R. dorsalis E3 ubiquitin ligase Seven in absentia (RdSina), while RdBV infection suppresses its expression. We show that RdSina directly targets and mediates the degradation of RSMV phosphoprotein (P), thereby attenuating the formation of P-induced viroplasm that are crucial for viral replication. RdSina interacts with nonstructural protein NSs2 of RdBV but does not mediate its ubiquitination. However, NSs2 competes with RSMV P for binding to RdSina, thus neutralizing RdSina’s ability in mediating P degradation. Furthermore, we find that the MYC transcription factor binds to the promoter sequences of RdSina, activating its transcription. However, NSs2 also directly binds to the same promoter sequences of RdSina and competitively suppresses MYC-activated RdSina transcription. Together, NSs2 obstructs the function of RdSina in mediating P degradation, ultimately promoting RSMV propagation in co-infected vectors. These findings elucidate how insect symbiotic viruses negatively regulate E3 ubiquitin ligases to benefit arbovirus transmission by co-infected insect vectors, which potentially is a common phenomenon in nature.